A case control study on physical health components and cardiometabolic risk markers among elderly - Che Hasan, Muhammad Kamil (2014)
Introduction: Cardiometabolic diseases remain the leading cause of death as well as disabilities in Malaysian population and the risk increases gradually with age. The challenge to the chronic health care in the clinical and research communities alike is to describe the suitable components of preventive, diagnostic, and therapeutic care especially for elderly in the society. Hence, assessing physical health components in the elderly may provide information to complement the physiological data and perhaps could be used to predict the health status among elderly. Beneficial effects of physical health on the risk of cardiometabolic diseases in elderly that may underlie this relationship are not well understood. Thus, the aim of this study was to explore the relationship between physical health components and cardiometabolic risk markers among elderly. Methods: Thirty-four patients with cardiometabolic disease and 34 healthy subjects aged 60-75 area Kuala Lumpur, Malaysia participated in this study. Participants had undergone a series of test which were cardiorespiratory endurance, muscular strength, muscular flexibility and agility. Blood pressure was measured on the following day. Ten milliliters of blood were collected after an overnight fast for analysis of cardiometabolic risk markers which includes high sensitivity CRP, lipid profiles, glucose, insulin and HOMA-IR. Spearman rho correlation was used to determine the relationship between these parameters. Results: Result showed a significant positive relationship between muscular strength with glucose (r=0.265, p=0.029) and muscular strength with blood pressure (r=0.318, p=0.008). Significant negative relationship were observed between muscular flexibility with insulin (r=-0.276, p=0.023), muscular flexibility with HOMA-IR (r=-0.291, p=0.061). Conclusion: Elderly with good muscular strength and flexibility components in physical health leads the potential of preventing the cardiometabolic diseases by reducing the cardiometabolic risk markers. Therefore, effective muscular strength and flexibility promotion strategies for physical health are urgently needed in preventing cardiometabolic diseases.